If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6k+31=-6k-6(-2k-6)
We move all terms to the left:
6k+31-(-6k-6(-2k-6))=0
We calculate terms in parentheses: -(-6k-6(-2k-6)), so:We get rid of parentheses
-6k-6(-2k-6)
We multiply parentheses
-6k+12k+36
We add all the numbers together, and all the variables
6k+36
Back to the equation:
-(6k+36)
6k-6k-36+31=0
We add all the numbers together, and all the variables
-5!=0
There is no solution for this equation
| 5y+35=5 | | 5b-3=2b | | -25y+13=38 | | E^(3x)-6=150 | | -3x+53+11x+21=90 | | 10(g-86)=8 | | 6y=30-12 | | 2t-5=t-2 | | b^2+28b-27=23 | | -8y-20=4 | | 16x-16=90 | | y=-2(1)^2-4(1) | | 2b+1=3b | | y=-2(1)^2-4(1 | | 2(x+7)-7=7 | | 16x-16+4x+26=90 | | 1=x-x^2 | | q^2-2q=15 | | 20y-30=20 | | 7w-6=4 | | 6y+9=15 | | 4=s+2 | | 10=2p/12 | | (14x-22)+(5+55)=90 | | 3x-7=16-2x | | 7x+2=20+x | | -2z+3+z=-12 | | x^2-25x-129=3 | | y=8.55+20 | | 20x-42=6x | | 3w=6w-45 | | h^2-18h=-20 |